2007
DOI: 10.4049/jimmunol.179.1.623
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sepsis Mortality Characterized by an Individualized Inflammatory Response

Abstract: Late mortality in septic patients often exceeds the lethality occurring in acute sepsis, yet the immunoinflammatory alterations preceding chronic sepsis mortality are not well defined. We studied plasma cytokine concentrations preceding late septic deaths (days 6–28) in a murine model of sepsis induced by polymicrobial peritonitis. The late prelethal inflammatory response varied from a virtually nonexistent response in three of 14 to a mixed response in eight of 14 mice to the concurrent presence of nearly all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 59 publications
4
71
0
Order By: Relevance
“…To study the kinetics and immunological properties of MDSCs in sepsis, we induced a sepsis response that develops in early and late phases. The early/acute phase of sepsis in mice is defined as the first 5 days after CLP (17,31). Our previous studies showed that the mortality rate in this model is ϳ20 to 30% during the early phase (days 1 to 5) of sepsis, and mice surviving the early phase develop late/prolonged bacterial infections and an immunosuppressive inflammatory phenotype, typical of late/ chronic sepsis (7).…”
Section: Cd11bmentioning
confidence: 99%
“…To study the kinetics and immunological properties of MDSCs in sepsis, we induced a sepsis response that develops in early and late phases. The early/acute phase of sepsis in mice is defined as the first 5 days after CLP (17,31). Our previous studies showed that the mortality rate in this model is ϳ20 to 30% during the early phase (days 1 to 5) of sepsis, and mice surviving the early phase develop late/prolonged bacterial infections and an immunosuppressive inflammatory phenotype, typical of late/ chronic sepsis (7).…”
Section: Cd11bmentioning
confidence: 99%
“…In many cases, determining what force dominates (pro-vs antiinflammatory responses) on the basis of serum measurements will remain nearly impossible, because both responses are enhanced during septic shock. An alternative would be to use a panel of markers rather than a single parameter, allowing a better definition of individualized pro-/anti-inflammatory profiles (49,(71)(72)(73).…”
Section: Measurement Of Circulating Mediatorsmentioning
confidence: 99%
“…Evidence supports that the pathophysiology of sepsis varies as it moves from an initiating early/acute hyperinflammatory phase to a late/chronic hypoinflammatory and immunosuppressive phase (31,47,51,67). The early phase of sepsis is typified by a systemic inflammatory response syndrome (SIRS) characterized by excessive production of proinflammatory mediators by neutrophils and macrophages (53), increased generation of reactive oxygen species, and leukocyte-induced microvascular injury and organ failure (35).…”
mentioning
confidence: 99%